2020
DOI: 10.1002/stc.2644
|View full text |Cite
|
Sign up to set email alerts
|

Input energy reduction principle of structures with generic tuned mass damper inerter

Abstract: The incorporation of the inerter with tuned mass damper yields the inerterbased tuned mass damper that has been verified as effective lightweight or performance-enhanced control devices. This study theoretically proved an intrinsic effect, namely, the input energy reduction, that the inerter reduces the input energy transmitted into the controlled structures from ground motion. A generic tuned mass damper inerter (GTMDI) including two separating inerters (the total inertance keeps constant) is analyzed to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Inerters are known as two-terminal devices whose terminals can move freely to provide a resisting force that is proportional to their relative acceleration due to its mass amplification effect [26][27][28]. In particular, these properties are often used in vibration reduction problems [29], where only by tuning the properties of the inerter device [30,31] one can achieve optimal vibration absorption [32]. The dynamic mass-amplifying effect of inerters was applied in [33] to investigate longitudinal elastic wave propagation characteristics of acoustic metamaterials with different inerter configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Inerters are known as two-terminal devices whose terminals can move freely to provide a resisting force that is proportional to their relative acceleration due to its mass amplification effect [26][27][28]. In particular, these properties are often used in vibration reduction problems [29], where only by tuning the properties of the inerter device [30,31] one can achieve optimal vibration absorption [32]. The dynamic mass-amplifying effect of inerters was applied in [33] to investigate longitudinal elastic wave propagation characteristics of acoustic metamaterials with different inerter configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Marian and Giaralis (2014) proposed to place an inerter between the primary structure and the mass of a conventional TMD to constitute a TMD inerter (TMDI) and used it to suppress the vibration of the stochastically support-excited structural system. Zhao et al (2021) studied the stochastic response and energy balance of the TMDI-equipped system and found that the inerter can reduce the input energy. Wang and Giaralis (2021) investigated the influence of the elastic and mass properties of the primary structure to TMDI control performance.…”
Section: Introductionmentioning
confidence: 99%
“…This paper compared the most important approaches and the methods exploiting the concept of control theory without adding new degrees of freedom into the system. In [25], a generic tuned mass damper inerter (GTMDI) is presented. In this study, an intrinsic effect of the reduction in the input energy of the structure based on GTMDI is proved: the inerter reduces the input energy, which is transmitted into the controlled structures.…”
Section: Introductionmentioning
confidence: 99%